Key enzyme systems controlling the oxidative stress in the psychrophilic eubacterium Pseudoalteromonas haloplanktis - E. DE VENDITTIS; R. COTUGNO; I. CASTELLANO; F. CECERE; P. GRIMALDI; I. RUGGIERO; I. BONIFACIO; G. SALOMONE; P. FALASCA; G. EVANGELISTA; A. MICHNIEWICZ; G. PARLATO; et al. (2007)
This work reports properties of typical enzyme redox systems in Pseudoalteromonas haloplanktis (Ph), a psychrophilic eubacterium isolated from marine Antarctic sediments. The enzymes investigated are superoxide dismutase (PhSOD) and the components of the thioredoxin system, namely thioredoxin (PhTrx) and thioredoxin reductase (PhTrxR), altogether involved in the homeostasis of reactive oxygen species (ROS). This control in P. haloplanktis is likely crucial, because of the increased oxygen solubility in cold sea water. The enzymatic defence includes a preventive action by PhSOD and the repair activity of the thioredoxin system. PhSOD was purified as a homodimeric iron-containing enzyme, displaying a high specific activity even at low temperatures. The enzyme keeps its activity at temperatures well above the maximum growth temperature of P. haloplanktis. Interestingly, PhSOD has a highly reactive cysteine covalently modified by β–mercaptoethanol or oxidized glutathione. The enzyme is also modified by peroxynitrite, a harmful ROS, which in other SODs reacts with a specific conserved tyrosine. These modifications regulate the PhSOD functions, acting on enzyme activity and/or sensibility toward physiological inactivators. Both components of the thioredoxin system in P. haloplanktis (PhTrxR and PhTrx) were obtained as recombinant His-tagged proteins. PhTrx is a small monomeric protein, whereas PhTrxR is a NADPH-dependent homodimeric flavoenzyme. When studying the effect of temperature on the PhTrxR activity, maximum levels were reached at 30°C. Concerning recombinant PhTrx, it reduces the insulin disulfide in the presence of DTT as electron donor. These key elements regulate the redox homeostasis in P. haloplanktis contribute to the efficient protection of this microorganism against ROS.